Key management for bitcoin transactions using cloud based key splitting technique - Buchade, Amar; Sharma, Nakul; Jadhav, Varsha; Nalavade, Jagannath; Sapate, Suhas; Sajjan, Rajani (Institute of Advanced Engineering and Science, 2025)
Bitcoin wallet contains the information which is required for making transactions. To access this information, user maintains the secret key. Anyone with the secret key can access the records stored in bitcoin wallet. The compromise of the key such as physical theft, side channel attack, sybil attack, DoS attack and weak encryption can cause the access of transactional details and bitcoins stored in the wallet to the attacker. The cloud-based key split up technique is proposed for securing the key in blockchain technology. The key shares are distributed across virtual machines in cloud computing. The approach is compared to the existing key management approaches such as local key storage, keys derived from password and hosted wallet. It is observed that our approach is most suitable among the other key management approaches.